Insomnia in patients treated with checkpoint inhibitors for cancer: A meta-analysis - Kiss, Igor; Kuhn, Matyas; Hrusak, Kristian; Buchler, Benjamin; Boublikova, Ludmila; Buchler, Tomas (Frontiers in Oncology, 2022)
Purpose: Insomnia in cancer patients is a common symptom contributing to poor quality of life and poor functioning. Sleep disturbances have been associated with inflammatory activity, and systemic cancer therapies chemotherapy, hormonal therapy, and immunotherapy may cause insomnia. We have carried out a meta-analysis to estimate the occurrence of insomnia in patients with solid cancer treated with immunotherapy using checkpoint inhibitors (CPI). Methods: PubMed and ClinicalTrials.gov were searched for phase 3 studies using a checkpoint inhibitor alone or in combination with chemotherapy or non-immunologic targeted therapy in the experimental arm and control arm using inactive therapies such as placebo or observation, chemotherapy, or non-immunologic targeted therapy. Adverse events listed in the full texts as well as those available from clinicaltrials.gov were reviewed for all included studies. Random effect logistic model was used to compare pooled data. Heterogeneity between studies was described using Cochrane Q statistics and I2 statistics. Results: A total of 54 studies (including six three-arm studies) involving 37,352 patients with evaluated toxicity were included in the analysis. Insomnia was reported in 8.3% of subjects (95% CI 8.0%-8.7%) treated with immunotherapy. Insomnia was significantly more common in patients receiving immunotherapy compared to those enrolled in study arms with inactive treatment (odds ratio [OR] 1.49, 95% confidence interval [CI] 1.13-1.96). The odds for insomnia were similar between the arms for CPI versus chemotherapy and CPI versus non-immunologic targeted therapies (OR 1.07, 95% CI 0.94-1.22 and OR 1.40, 95% CI 0.90-2.18, respectively). The highest OR for insomnia using antiPD1 agents as reference was detected for the combination of antiCTLA4 and antiPD-1/L1 agents (OR 1.36, 95% CI 1,06 – 1,74). The OR was also higher for the combination of antiCTLA4 and antiPD-1/L1 therapy compared to antiPD-1/L1 drugs (OR 1.36, 95% CI 1.05-1.75). Conclusion: Cancer immunotherapy using CPI is associated with insomnia but the odds of developing the symptom are not greater with immunotherapy than with other systemic modalities including chemotherapy and non-immunologic targeted therapies.